PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN DI PT. BANK MALUKU MALUKU UTARA CABANG TERNATE - Esa, Farnida; Marwan, Marwan; Nurlaila, Nurlaila (Jurnal MS, 2020)
Objective: The purpose of this study are: (1) To determine and analyze the effect of workload on employee performance at PT. Bank Maluku North Maluku Ternate Branch; (2) To find out and analyze the effect of work stress on the performance of employees of PT. Bank Maluku North Maluku Ternate Branch; and (3) To find out and analyze the effect of workload and work stress on employee performance at PT. Bank Maluku North Maluku Ternate Branch. The number of research samples was 43 employees. Bank Maluku North Maluku Ternate Branch. Methodology: The test equipment used is multiple linear regression analysis (multiple regression) using statistical package for social scientists (SPSS) as a statistical test tool. Finding: H1 H2, and H3 are accepted at the 5% confidence level Conclusion: The results of the study show that: (1) workload has a positive and significant effect partially on employee performance at PT. Bank Maluku North Maluku Ternate Branch. The results of this study mean that, employee workload is able to improve employee performance; (2) Job stress has a positive and significant effect partially on employee performance at PT. Bank Maluku North Maluku Ternate Branch. The results of this study mean that, the work stress experienced by employees is able to improve employee performance; and (3) Workload and work stress simultaneously have a positive and significant effect on PT. Bank Maluku North Maluku Ternate Branch.